2021
DOI: 10.1021/acs.analchem.0c04525
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Screening of Polycyclic Aromatic Hydrocarbons and Similar Compounds Using GC–APLI–TIMS–TOFMS/GC–EI–MS

Abstract: In the present work, a novel workflow based on complementary gas-phase separations for the identification of isomeric PAHs from complex mixtures is described. This is the first report on the coupling of gas chromatography (GC), atmospheric pressure laser ionization (APLI), and trapped ion mobility spectrometry–mass spectrometry (TIMS–MS) for the characterization of polycyclic aromatic hydrocarbons. Over a hundred known unknowns are uniquely identified based on the molecular ion retention indices I (5%), mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 70 publications
2
35
0
Order By: Relevance
“…All standards were diluted in hexane before use to a final concentration of 4 mg/L. Details on the preparation of deasphalted crude oil samples can be found elsewhere . Briefly, 50 mg of the crude oil was carefully weighed and mixed with 100 μL of the deuterated PAHs (Table S1 of the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All standards were diluted in hexane before use to a final concentration of 4 mg/L. Details on the preparation of deasphalted crude oil samples can be found elsewhere . Briefly, 50 mg of the crude oil was carefully weighed and mixed with 100 μL of the deuterated PAHs (Table S1 of the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that atmospheric pressure laser ionization (APLI) is more suitable for accessing the PAH content in crude oils . With the coupling of GC–APLI, the characterization of PAH-like components using commercial MS analyzers was realized. , Recently, we described the advantages of complementary gas-phase separations for the identification of isomeric PAHs from complex mixtures using GC–APLI–TIMS–TOF MS; noteworthy is the analytical capability for untargeted screening of isomeric and isobaric compounds not available in traditional GC–EI–MS n workflows.…”
Section: Introductionmentioning
confidence: 99%
“…They used an in-house database consisting of 800 CCS values to screen for drug-like compounds and pesticides [21]. Recently, Olanrewaju et al [95] have analyzed PAHs and related petroleum hydrocarbons in crude oil using a trapped ion mobility-mass spectrometer hyphenated with GC. In this study, the identification of isomeric PAHs and related unknown aromatic hydrocarbons was accomplished with the aid of CCS measurements.…”
Section: Data-independent Identificationmentioning
confidence: 99%
“…In this context, Barrow et al first brought GC–APCI to high-resolution mass spectrometric detection for the characterization of oil sands, whereas Benigni et al showed the sensitivity of APLI toward polycyclic aromatic hydrocarbons in GC–APLI high-resolution mass spectrometry . Very recently, the Fernandez-Lima group expanded the analytical performance for hydrocarbon speciation by additional integration of ion mobility separation . Integration of fast ion mobility separation (∼milliseconds) creates new capabilities for untargeted screening of the isomeric and isobaric complexity.…”
Section: Pyrolysis and Gas Chromatography Mass Spectrometry (Pyr–gcms...mentioning
confidence: 99%
“…34 Very recently, the Fernandez-Lima group expanded the analytical performance for hydrocarbon speciation by additional integration of ion mobility separation. 92 Integration of fast ion mobility separation (∼milliseconds) creates new capabilities for untargeted screening of the isomeric and isobaric complexity. In particular, the collision cross-section (CCS) information retrieved from ion mobility spectrometry adds an additional metric not accessible by classical fragmentation and tandem mass spectrometry.…”
Section: ■ Synchrotron Radiation Photoionizationmentioning
confidence: 99%